(untitled) (Annals of Medical Research, 2026)
Aim: Peripheral T-cell lymphoma (PTCL) is a rare and aggressive subtype of non-Hodgkin lymphoma with limited treatment options, particularly in relapsed/refractory (R/R) cases. Belinostat, a pan-histone deacetylase inhibitor, has emerged as a potential therapeutic agent in this setting. Materials and Methods: This retrospective study analyzed nine patients with relapsed/refractory PTCL treated with belinostat across three centers between 2018 and 2025. Clinical data and treatment outcomes were collected, and responses were evaluated using the Lugano criteria. Overall survival and progression-free survival were calculated with the Kaplan–Meier method. Results: Of the nine R/R PTCL patients treated with belinostat, two (22.2%) achieved complete remission (CR), one (11.1%) experienced stable disease, four (44.4%) developed progressive disease and two (22.2%) died from lymphoma progression before the second cycle could be administered. Notably, one patient maintained a prolonged CR through 14 belinostat cycles, while another continued to use belinostat as a bridge to allogeneic stem cell transplantation and as maintenance after allogeneic transplantation. Belinostat was generally well tolerated, and no treatment discontinuations or dose reductions were required due to adverse events. Conclusion: Although these real‐world findings suggest that belinostat may provide meaningful clinical benefit in a subset of heavily pretreated R/R PTCL patients, the high rate of early progression emphasizes the need for improved patient selection and prospective validation in larger studies.